DA white dwarfs from the LSS-GAC survey DR1: the preliminary luminosity and mass functions and formation rate - Rebassa-Mansergas, A; X -W Liu; Cojocaru, R; H -B Yuan; Torres, S; Garcia-Berro, E; Xiang, M -X; Huang, Y; Koester, D; Hou, Y; G Li; Zhang, Y (arXiv.org, 2015)
Modern large-scale surveys have allowed the identification of large numbers of white dwarfs. However, these surveys are subject to complicated target selection algorithms, which make it almost impossible to quantify to what extent the observational biases affect the observed populations. The LAMOST (Large Sky Area Multi-Object Fiber Spectroscopic Telescope) Spectroscopic Survey of the Galactic anti-center (LSS-GAC) follows a well-defined set of criteria for selecting targets for observations. This advantage over previous surveys has been fully exploited here to identify a small yet well-characterised magnitude-limited sample of hydrogen-rich (DA) white dwarfs. We derive preliminary LSS-GAC DA white dwarf luminosity and mass functions. The space density and average formation rate of DA white dwarfs we derive are 0.83+/-0.16 x 10^{-3} pc^{-3} and 5.42 +/- 0.08 x 10^{-13} pc^{-3} yr^{-1}, respectively. Additionally, using an existing Monte Carlo population synthesis code we simulate the population of single DA white dwarfs in the Galactic anti-center, under various assumptions. The synthetic populations are passed through the LSS-GAC selection criteria, taking into account all possible observational biases. This allows us to perform a meaningful comparison of the observed and simulated distributions. We find that the LSS-GAC set of criteria is highly efficient in selecting white dwarfs for spectroscopic observations (80-85 per cent) and that, overall, our simulations reproduce well the observed luminosity function. However, they fail at reproducing an excess of massive white dwarfs present in the observed mass function. A plausible explanation for this is that a sizable fraction of massive white dwarfs in the Galaxy are the product of white dwarf-white dwarf mergers.